FINANCING OF RURAL DEVELOPMENT AND ECONOMIC PERFORMANCES INRURAL AREAS OF BOSNIA AND HERZEGOVINA - Ramić, Edin; Vasiljević, Zorica (Economics of Agriculture, 2009)
Rural economy of Bosnia and Herzegovina (B&H), which is shaped and supported by agribusiness development, has been faced with several goals, that are very important for development of the country, and those are the following: to create possibilities for income creation in agricultural sector, to support process of the refugees' return as well as to "unload" urban settlements, to enable appropriate quantities of healthy food under competitive prices, to strengthen domestic market by decrease of food trade debalance, to enable development of tourism as well as other corresponding economic branches. Stabilization and Association Agreement sets additional challenges in front of rural community and agribusiness sector. The agribusiness sector and rural economy have to be ready for adaptation according to new legislative as well as EU standards, which requires a huge transfer of technology as well as strengthening of human resource potentials. Policy of agricultural and rural development in Bosnia and Herzegovina could be well followed by analysis of the budgets made by particular strategies' decision makers and this analysis is one of the main topics this paper is dealing with. Beside analysis of funds assigned to rural sector and agricultural development, it is also important to analyze utilization of those resources, because the basic problem of B&H agrarian policy is not only in lack of resources, but in utilization of modern policy instruments oriented toward capacity improvement as well as establishment of the business operation environment.